2020
DOI: 10.1097/prs.0000000000006550
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Tissue Expansion: Predictors of Premature Expander Removal in a Single Surgeon’s Experience with 472 Expanders

Abstract: Background: Tissue expansion is used for soft-tissue reconstruction in pediatric patients. The expansion process can be complicated by infection and extrusion, leading to premature expander removal. The aim of this study was to identify risk factors associated with premature expander removal caused by infection or extrusion in pediatric patients. Methods: A retrospective study of pediatric patients who underwent tissue expansion performed by the senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 19 publications
2
46
2
Order By: Relevance
“…Multiple expander placement is commonly reported ranging from 2 to 6 expanders, with Wang and colleagues reporting an average of 1.7 ± 0.6 expanders placed per operation. 8,14 Seventynine patients had multiple TE placed in our cohort accounting for 19.7%, but remarkably, only 14.3% of those with complications had multiple TE. Studies have reported differing conclusions on the safety profile of multiple expansions.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Multiple expander placement is commonly reported ranging from 2 to 6 expanders, with Wang and colleagues reporting an average of 1.7 ± 0.6 expanders placed per operation. 8,14 Seventynine patients had multiple TE placed in our cohort accounting for 19.7%, but remarkably, only 14.3% of those with complications had multiple TE. Studies have reported differing conclusions on the safety profile of multiple expansions.…”
Section: Discussionmentioning
confidence: 73%
“…5,6,[12][13][14] The overall complication rate of 5.7% reported in the NSQIP-P was much lower than rates between 12% and 40% described in smaller single-site retrospective reviews. 14,15 As with other studies using NSQIP-P, complications are typically recorded by staff who are not surgeons based on keywords and codes from the electronic medical record. This can lead to underreporting or inaccurate reporting of complication rates.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Wang et al (2019) reported a complication rate of 16.5% in scalp reconstruction with the staged tissue expansion method. (15) Tissue growth can impose pressure on the underlying dura/brain in the event of pre-existing cranial anomalies. (16,17) In the context of cranioplasty reconstruction, free tissue transfer is typically recognized as the optimal approach to restoration for large-scale scalp covering.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue expanders may be undesirable for some patients as they have an associated 16.5% complication rate and can elicit significant discomfort for the patient. 42 When an underlying vascular bed is unavailable, local pedicled flaps or free tissue transfer is needed (►Fig. 8).…”
Section: Tumorsmentioning
confidence: 99%